"Talks with students Varanasi, (1954)" - "Krishnamurti, J." (Chennai, 2012)
This book contains authentic reports of J. Krishnamurti$1 (Bs talks and dialogues with students, held in Varanasi in January 1954. Fifteen of these talks were given at the Rajghat Besant School, which he had founded at the confluence of the Ganga and Varuna, and three at the Banaras Hindu University. In all these, he shares with his listeners his central vision that education should not be separated from life and that it must help the young and the old to understand not merely the outer world, but also the inner world of human consciousness. Emphasizing that life is relationship, he said education must help the young to discover their right relationship with nature, with society, with fellow beings, with knowledge, and with themselves.s
Keywords: Indian philosopy